P195 Plume characteristics of fluticasone propionate/formoterol pMDI compared with fluticasone propionate/salmeterol pMDI. (14th November 2013) - Johal, B; Murphy, S; Marshall, J
Abstract : Background: It has been suggested that aerosol inhaler characteristics such as fine particle size distribution, low plume velocity, and long duration of the aerosol cloud may assist coordination of inhalation with actuation, improve lung deposition, and reduce oropharyngeal deposition. This study compared 2 ICS/LABA combination HFA pMDI inhalers: fluticasone propionate/formoterol 125/5 μg (FP/FORM; flutiform ® ) and fluticasone propionate/salmeterol 125/50 μg (FP/SAL; Seretide ® Evohaler ® ). Methods: Inhalers were operated according to their respective patient information leaflets, and were fired into still air. Plume data were recorded using an Oxford Lasers EnVision Pharma system with high speed CMOS camera and short-pulse laser light source. VidPIV 4.6 & EnVision 1.1.5 software was used to analyse the data and assess velocity and other characteristics of the plume at set intervals from the actuator (up to 9.5 cm which is representative of the distance from mouth to throat). Results: FP/FORM pMDI had slower maximum velocity of plume than did FP/SAL at the distances measured (table). Furthermore, the duration of plume lasted approximately 50% longer over the distance measured with FP/FORM than with FP/SAL. Conclusion: FP/FORM has a slower and more prolonged plume compared with FP/SAL. This may help synchronise aerosol availability and inhalation and may lead to less oropharyngeal deposition and better lung deposition.